Estimates of total body iron indicate 19 mg and 38 mg oral iron are equivalent for the mitigation of iron deficiency in individuals experiencing repeated phlebotomy. Issue 9 (9th June 2017) - Bialkowski, Walter; Kiss, Joseph E.; Wright, David J.; Cable, Ritchard; Birch, Rebecca; D'Andrea, Pam; Bryant, Barbara J.; Spencer, Bryan R.; Mast, Alan E.
Abstract : Iron deficiency anemia is a common clinical condition often treated with tablets containing 65 mg of elemental iron. Such doses can elicit gastrointestinal side effects lowering patient compliance. Oral iron supplements also increase hepcidin production causing decreased fractional absorption of subsequent doses. Frequent blood donors often become iron deficient. Therefore, they were enrolled in a two‐year study involving continued blood donations and randomization to receive no pill, placebo, 19, or 38 mg ferrous gluconate for 60 days. Total body iron (TBI) did not change for the subset of donors in the no pill and placebo groups who completed both enrollment and final visits ( P  = .21 and P  = .28, respectively). However, repeated measures regression analysis on the complete dataset estimated a significant decrease in TBI of 52 mg/year for the placebo and no pill groups ( P  = .001). The effects of 19 and 38 mg iron supplementation on TBI were indistinguishable ( P  = .54). TBI increased by 229 mg after the initial 60 days of iron supplementation ( P  < .0001) and was maintained at this higher level with continued iron supplementation following each subsequent donation. The TBI increase was apportioned 51 mg to red cell iron ( P  < .0001) and 174 mg to storage iron ( P  < .0001). Changes in storage iron were negatively impacted by 57 mg due to concurrent antacid use ( P  = .04). These findings in blood donors suggest that much lower doses of iron than are currently used will be effective for clinical treatment of iron deficiency anemia.